2014
DOI: 10.1186/1756-0500-7-555
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic pitfalls of hyperprolactinemia: the importance of sequential pituitary imaging

Abstract: BackgroundThe purpose of this study is to confirm whether the serum prolactin cut-off value is definitive to distinguish prolactinoma and non-functioning pituitary adenoma with hyperprolactinemia. We retrospectively reviewed patients with non-functioning pituitary adenoma, including gonadotroph cell adenoma, null cell adenoma and prolactinoma who were surgically treated at Kohnan hospital between June 2005 and March 2012. The patients without endocrinological/neurological symptom and with the tumor larger than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 21 publications
1
7
0
1
Order By: Relevance
“…Significant elevation of prolactin is >200 ug/L (>200 ng/mL) and is almost invariably indicative of a prolactin secreting pituitary adenoma. 23 , 24 A “stalk effect” secondary to a large sellar mass as in this case may also increase serum prolactin levels due to obstruction of inhibitory dopamine flow from the hypothalamus. The elevation would usually fall between 96-200ng/mL and would not be too elevated, thus this was ruled out.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Significant elevation of prolactin is >200 ug/L (>200 ng/mL) and is almost invariably indicative of a prolactin secreting pituitary adenoma. 23 , 24 A “stalk effect” secondary to a large sellar mass as in this case may also increase serum prolactin levels due to obstruction of inhibitory dopamine flow from the hypothalamus. The elevation would usually fall between 96-200ng/mL and would not be too elevated, thus this was ruled out.…”
Section: Discussionmentioning
confidence: 93%
“…The elevation would usually fall between 96-200ng/mL and would not be too elevated, thus this was ruled out. 24 All other causes for hyperprolactinemia were ruled out in this case. Evaluation of the hormones involved in the hypothalamus-pituitary-endocrine gland axis is imperative (Table 2).…”
Section: Discussionmentioning
confidence: 93%
“…For a PRL cut-off value of 204 μg/L (4338 mU/L), both sensitivity and specificity of diagnosing a macro adenoma were optimal. While several studies assess the cut-off PRL value that could differentiate between a prolactinoma and a non-functioning pituitary adenoma 9 , 14 , 15 , and cut-off differentiating between a prolactinoma and “stalk effect” hyperprolactinemia, to the best of our knowledge, this is the first study reporting on a value that distinguishes micro- from macro- prolactinomas. In other studies, the cut off for distinguishing a true macroprolactinoma from a non-functioning pituitary adenoma (NFPA) was typically > 189 μg/L (> 4000 mU/L) 16 .…”
Section: Discussionmentioning
confidence: 99%
“…However, in clinical practice, the optimal PRL level for the differential diagnosis of prolactinoma and other types of pituitary adenoma is far from 250 µg/l. Kawaguchi et al (28) reported that the optimal PRL level for the differential diagnosis of prolactinoma and non-functioning adenomas was 38.6 µg/l, which is substantially lower than 100-200 ng/ml. Karavitak et al (6) demonstrated that the PRL level of non-functional pituitary adenomas did not exceed 2,000 mIU/l (1 µg/l=21.2 mIU/l), and 2,000 mIU/l was considered as the upper PRL limit of non-functional pituitary adenomas.…”
Section: Discussionmentioning
confidence: 99%